The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/cssc.201402070
|View full text |Cite
|
Sign up to set email alerts
|

Green Acetylation of Solketal and Glycerol Formal by Heterogeneous Acid Catalysts to Form a Biodiesel Fuel Additive

Abstract: A glut of glycerol has formed from the increased production of biodiesel, with the potential to integrate the supply chain by using glycerol additives to improve biodiesel properties. Acetylated acetals show interesting cold flow and viscosity effects. Herein, a solventless heterogeneously catalyzed process for the acetylation of both solketal and glycerol formal to new products is demonstrated. The process is optimized by studying the effect of acetylating reagent (acetic acid and acetic anhydride), reagent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 21 publications
0
22
0
1
Order By: Relevance
“…They are shown to have good solubility and stability towards oxidation but hydrolyze in the presence of acid [4] . This class of compound and its derivatives also have shown potential in different applications including as surfactant, [5] fuel additives [6–8] and anti‐freezing agent [9,10] . Dodson et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are shown to have good solubility and stability towards oxidation but hydrolyze in the presence of acid [4] . This class of compound and its derivatives also have shown potential in different applications including as surfactant, [5] fuel additives [6–8] and anti‐freezing agent [9,10] . Dodson et al.…”
Section: Introductionmentioning
confidence: 99%
“…[3] They are shown to have good solubility and stability towards oxidation but hydrolyze in the presence of acid. [4] This class of compound and its derivatives also have shown potential in different applications including as surfactant, [5] fuel additives [6][7][8] and anti-freezing agent. [9,10] Dodson et al (2014b) showed the anti-oxidant activity exhibited by aromatic glycerol acetal indicated wide range of potential of this class of compound in industrial application including biodiesel industry.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been carried out on transformation of glycerol into valuable products, such as glycerol carbonate [16][17][18] and solketal [19][20][21][22]. Glycerol carbonate has applications as a curing agent in cement and concrete building, solvent for active medical ingredients in various pharmaceutical formulations, an electrolyte in lithium and lithium-ion batteries, and in production of various polymers and plastics [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25] Glycerol esters, ketals and ethers are commonly used as solvents and additives in cleaning, cosmetic, food and pharmaceutical industry. [26][27][28][29][30] Glycerol ethers stand out among other glycerol derivatives by their relative chemical inertness, which make them very suitable as solvents. Apart from the synthesis of glycerol tertbutyl ethers from glycerol and isobutene, deeply studied due to their use as biofuel additives, 31 the synthesis of alkyl glyceryl ethers from glycerol has been investigated in order to obtain a large class of compounds with tunable properties depending on the number and nature of the alkyl chains.…”
Section: Introductionmentioning
confidence: 99%